2018
DOI: 10.3390/ijms19103283
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Brassinosteroids and Ethylene during Plant Growth and under Abiotic Stress Conditions

Abstract: Plant hormones through signaling networks mutually regulate several signaling and metabolic systems essential for both plant development and plant responses to different environmental stresses. Extensive research has enabled the main effects of all known phytohormones classes to be identified. Therefore, it is now possible to investigate the interesting topic of plant hormonal crosstalk more fully. In this review, we focus on the role of brassinosteroids and ethylene during plant growth and development especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 47 publications
(61 reference statements)
0
31
0
1
Order By: Relevance
“…To date, extensive studies have shown that BRs play critical roles in modulating plant growth and development. In recent years, BR was also reported to increase plant tolerance to adverse environments, such as salt, drought, and cold temperatures [ 20 , 40 42 ]. The transcription factors BRASSINAZOLE RESISTANT 1, BRI1 EMS SUPPRESSOR 1, and CESTA, all well characterized as being BR-controlled [ 26 28 ], can enhance freezing tolerance through both CBF-dependent and CBF-independent pathways [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, extensive studies have shown that BRs play critical roles in modulating plant growth and development. In recent years, BR was also reported to increase plant tolerance to adverse environments, such as salt, drought, and cold temperatures [ 20 , 40 42 ]. The transcription factors BRASSINAZOLE RESISTANT 1, BRI1 EMS SUPPRESSOR 1, and CESTA, all well characterized as being BR-controlled [ 26 28 ], can enhance freezing tolerance through both CBF-dependent and CBF-independent pathways [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of BRs to cucumber seedlings showed increased levels of ethylene and alternative oxidase pathway (AOX) components. BRs also help in avoiding oxidative damage done by ROS as it initiates the production of ethylene and ROS, which in turn activates AOX, leading to the detoxification of excess ROS produced [174]. BR and ethylene act synergistically in overcoming the adverse effects of salinity during seed germination.…”
Section: Jasmonic Acid Brassinosteroids and Ethylenementioning
confidence: 99%
“…This was also in contradiction with the overall positive influence that BRs had in various plant models, including tomato (Bitterlich et al, 2014a(Bitterlich et al, , 2014bFoo et al, 2016;Tofighi et al, 2017). However, most of this information was obtained using BR-deficient mutants under experimental conditions that may have influenced other plant hormones (e.g., ethylene; Jiroutova, Oklestkova & Strnad, 2018), known to affect mycorrhizal colonization. Another possible drawback was that the effect on AMF colonization was revealed only after BR levels were severely reduced (Foo et al, 2013).…”
Section: Ion Identitymentioning
confidence: 91%